Gambaran perawatan pencabutan gigi dan tingkat pengetahuan masyarakat tentang kesehatan gigi dan mulut di wilayah kerja Puskesmas Mengwi II - Ni Putu Novi Wiantari; Putu Ika Anggaraeni; Steffano Aditya Handoko (Bali Dental Journal, 2018)
Background: Tooth extraction is a procedure of pulling out the teeth from the alveolar bone socket. Tooth extraction is a last choice of treatment for the patients that have damaged tooth and cannot be treated anymore. Aim: The purpose of this study was to determine the level of society knowledge about oral health for the tooth extraction treatment in Puskesmas Mengwi II. Methods: A descriptive study with cross sectional approach was done from October 24 to November 30, 2016 at Puskesmas Mengwi II. Data were collected by means of questionnaires. Total sample of 76 respondents were patients aged 18 years and older who performed dental and oral treatment at Puskesmas Mengwi II. Statistical analysis of univariate and bivariate (chi square test) are used to determine the relationship between 2 variables.Results: The results of this study are 16 (21.1%) respondents performed tooth extractions and 60 (78.9%) respondents did not perform tooth extractions. There are 52 (68.4%) respondents with high level of oral health knowledge and 24 (31.6%) respondents with low level of oral health knowledge. Chi square test analysis showed the value of p = 0.019. Conclusions: It was concluded that respondents with low level of oral health knowledge have a higher proportion of tooth extraction compared with high level of oral health knowledge and it is statistically significant.